Dietary and plasma atherogenic and thrombogenic indices and cardiometabolic risk factors among overweight and individuals with obesity - Reyhaneh Mokhtari; Mahdieh Abbasalizad Farhangi (BMC Endocrine Disorders)
Abstract Background Obesity and hyperlipidemia are the two central metabolic disorders linked to non-communicable diseases (NCDs) that increase the risk of cardiovascular disease (CVD). Apart from dyslipidemia, the Atherogenic Index of Plasma (AIP), which is associated with dietary consumption, is another marker for predicting the risk of CVD. Healthy fat quality indicators may impact AIP. The purpose of this study is to ascertain whether there is any connection between Iranian obese people’s plasma and dietary indices and cardiometabolic risk factors. Methods This cross-sectional study, consisted of 645 overweight and obese participants. The study included assessments of body composition and anthropometric measurements. Dietary fatty acid consumption was evaluated using a validated Food Frequency Questionnaire (FFQ) containing 168 items. Additionally, biochemical parameters, including serum total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), fasting serum glucose (FSG), and insulin levels, were measured using enzymatic methods. The lipid profile was quantified. Results For participants in higher tertiles of the AIP, the percentage of men was significantly higher than women (men: 48.1%, women: 51.7%, p < 0.001). Additionally, individuals in higher tertiles of AIP had a higher waist-to-hip ratio (WHR) (mean WHR: 0.92 ± 0.05 vs. 0.86 ± 0.04 in lower tertile, p < 0.001). Participants in the highest tertile of AIP had higher systolic blood pressure (SBP: 132 ± 8 mmHg vs. 118 ± 6 mmHg in lower tertile, p < 0.001), total cholesterol (TC: 210 ± 15 mg/dL vs. 185 ± 12 mg/dL, p < 0.001), triglycerides (TG: 180 ± 20 mg/dL vs. 120 ± 15 mg/dL, p < 0.001), and glucose concentrations (fasting glucose: 105 ± 10 mg/dL vs. 90 ± 8 mg/dL, p < 0.001). Participants in the lower tertile of AIP had higher HDL cholesterol levels (HDL: 60 ± 5 mg/dL vs. 45 ± 4 mg/dL in higher tertile, p < 0.001). In the model for Thrombogenicity Index (TI), participants in the higher tertile had higher glucose concentrations (glucose: 110 ± 12 mg/dL vs. 95 ± 9 mg/dL in lower tertile, p = 0.04). Conclusion This research introduces a novel field of investigation and emphasizes the possible importance of TI, AI, and AIP indices in regulating cardiometabolic risk factors.